ISU MUTAKHIR PENGARUH PENERAPAN KESEHATAN KESELAMATAN KERJA (K3) DI BERBAGAI BIDANG INDUSTRI - Oppy Oktavianty Windari; Susilawati (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2025)
This study aims to analyze the effect of Occupational Health and Safety (OHS) implementation in various industrial sectors. Industry is an important sector in the economy, but it also has high potential hazards for workers. Occupational diseases and accidents still occur frequently, so the implementation of OSH has an important role in order to protect workers and improve their welfare. This research applied a qualitative method with a literature study approach. Data were taken from various sources such as books, scientific journals, and related regulations. The results show that effective OHS implementation in various industrial sectors can provide various benefits, both for companies and workers. However, the implementation of OSH in various industrial sectors continues to face many challenges such as low knowledge and awareness of the importance of OSH, limited resources, and resistance from management and workers to changes in work procedures. Therefore, better efforts are needed from all concerned parties to develop and implement more effective OSH in various industrial sectors.